The Effects of a Nutrition Education Program on Dietary Intake and Biomarkers in HIV+ Adults. Issue 4 (July 2022) - Poles, Jillian; Tiozzo, Eduard; Konefal, Janet; Rodriguez, Allan; Woolger, Judi M.; Lewis, John E.
Background. People living with HIV (PLWH) have increased risk of cardiovascular disease (CVD). Dietary behavior modification may assist in the treatment of CVD, but the optimal dose of nutrition education is unknown. The current aim was to determine if a weekly 1-hour nutrition education program would improve multiple outcomes among PLWH. Methods. Participants (n = 62) were assessed on dietary intake, serum biomarkers, and physical characteristics at baseline and 3 months, and percent change was calculated. Participants were grouped into 3 attendance categories of the classes: none, fair, or good. Analyses of covariance were performed on the outcomes. Results. Calories, protein, fat, saturated fat, carbohydrate, sugar, added sugar, and glycemic load were significantly different (all P values <.05). Those who attended no class typically had increases in these variables versus those with fair or good attendance. High-density lipoprotein cholesterol (HDL-C; P = .006) and total cholesterol/HDL-C ratio ( P = .083) were different, as those who attended no class or had fair attendance worsened, but those with good attendance improved. Conclusions. Several outcomes improved more so among those with good class attendance versus those with either fair or no attendance. Thus, an interactive nutrition education program may be an effective tool to help improve the health of PLWH.